Poly(amidehydroxyurethane) template magnetite NPs electrosynthesis. II. Core and shell characterization - Laura Ursu (Memoirs of the Scientific Sections of the Romanian Academy, 2013)
Core and layer polymer characterization of magnetite nanoparticles (NPs) surface-functionalized with poly(amidehydroxyurethane) (PAmHU), obtained by a new electrochemical synthesis route is presented. The core magnetic properties were investigated by Vibrating Sample Magnetometer (VSM), showing that the obtained NPs have superparamagnetic to ferromagnetic behaviour (very low coercivity and remanence). The magnetite–PAmHU NPs morphology and size were studied by Atomic Force Microscopy (AFM) and Dynamic Light Scattering (DLS); both methods showed the existence of PAmHU out-flaked layer on NPs. Structural analysis by Infrared spectroscopy (FTIR) and Thermogravimetry (TG) confirm the out-flaking of magnetic NPs with PAmHU.